Effect of environmental awareness on purchase intention and satisfaction pertaining to electric vehicles in Japan. (February 2019) - Okada, Takanori; Tamaki, Tetsuya; Managi, Shunsuke
Highlights: This study investigates the purchase intentions of non-EV owners and the post-purchase satisfaction of EVs owners. SEM analysis shows that environmental awareness directly affects the purchase intentions. Environmental awareness does not have any direct effects on post-purchase satisfaction. Abstract: The reduction of CO2 emission using electric vehicles (EVs) is attracting much attention as a countermeasure for global warming. In this study, we investigate the intention of non-EV owners and the post-purchase satisfaction of EV owners by conducting online survey in Japan. The structural relation of both these factors is analyzed using structural equation modeling (SEM). This analysis focuses on the environmental awareness. We compare the estimations between the purchase intentions of non-EV users and the post-purchase satisfaction of EV users. Results show that the structures of purchase intentions of non-EV users and post-purchase satisfaction of EV are different. The evaluation of EVs shows that the environmental awareness has a direct effect on the purchase intention of a non-EV user, whereas an indirect effect on the post-purchase satisfaction of a EV user.